The Impact of Islamic Banking Financing on Economic Growth in Indonesia - Teapon, Rizal Rahman H; Evalia, Nur Afni (Jurnal Economia, 2025)
The optimization of the financial intermediation function is one of the primary goals of Law Number 4 of 2023. This regulation assigns a role to Islamic banking in carrying out intermediation, including financing. Therefore, this study aimed to determine the effects of Islamic banking financing on economic growth in Indonesia, using Novel Dynamic ARDL Simulation approach with time series data from 2009Q1 to 2022Q4. The results showed that work capital (WCP) and investment (INV) were significantly, positively, and dynamically related to economic growth (GDP) in the short and long terms, with consumption (CON) having a relevant and negative association. Policy simulation scenarios also proved that a 5% increase in WCP and INV encouraged GDP to the 20th quarter of the experimental year. In this context, the marginal impact of the variables sustained long-term economic growth in a positive trend after financing threshold point.